1982
DOI: 10.1042/bj2010199
|View full text |Cite
|
Sign up to set email alerts
|

Structural studies of the carbohydrate moieties of lectins from potato (Solanum tuberosum) tubers and thorn-apple (Datura stramonium) seeds

Abstract: 1. Methylation analysis of potato (Solanum tuberosum) lectin and thorn-apple (Datura stramonium) lectin confirmed previous conclusions that both glycoproteins contained high proportions of l-arabinofuranosides and lesser amounts of d-galactopyranosides. The arabinofuranosides are present in both lectins as short unbranched chains containing 1-->2- and 1-->3-linkages, which are known to be linked to hydroxyproline. Galactopyranosides are present as monosaccharides, which are known to be attached to serine, in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(37 citation statements)
references
References 32 publications
(58 reference statements)
2
35
0
Order By: Relevance
“…Ashford et al (5) reported that fungus ␣-L-arabinofuranosidase hydrolyzed Ara 4 -Hyp to Ara 3 -Hyp. Because HypBA2 cannot hydrolyze Ara 4 -Hyp, ␣-L-arabinofuranosidase will be needed for effective degradation of ␤-L-arabinofuranosides.…”
Section: Discussionmentioning
confidence: 99%
“…Ashford et al (5) reported that fungus ␣-L-arabinofuranosidase hydrolyzed Ara 4 -Hyp to Ara 3 -Hyp. Because HypBA2 cannot hydrolyze Ara 4 -Hyp, ␣-L-arabinofuranosidase will be needed for effective degradation of ␤-L-arabinofuranosides.…”
Section: Discussionmentioning
confidence: 99%
“…Cystine was determined as cysteic acid after performic-acid oxidation of the protein and subsequent hydrolysis at 10°C in constant-boiling HCI (6). Amino acids were measured on a Locarte Mini amino acid analyzer by reaction with ninhydrin; details of the elution programs which were used have been given elsewhere (2,3). Neutral sugars were measured by GLC on a Perkin-Elmer gas chromatograph fitted with flame ionization detectors after methanolysis (4 h at 85C) and trimethylsilylation ofthe glycoproteins (5).…”
Section: Methodsmentioning
confidence: 99%
“…Extensin and Solanaceae lectins contain repetitive Ser-Hyp 4 motifs with Hyp residues that are O-glycosylated with 1-4 arabinofuranosyl (Araf) residues with β-L-arabinofuranosyl linkages. The structures of Ara 3 -Hyp and Ara 4 -Hyp, which are the major constituents of Hyp-linked β-Larabinofuranosides in dicotyledons (7), are Arafβ1-2Arafβ1-2Arafβ-Hyp and Arafα1-3Arafβ1-2Arafβ1-2Arafβ-Hyp, respectively (8,9). However, despite the broad distribution of Hyp-linked β-L-arabinofuranosides in plant cells, degradative enzymes have not been identified yet.…”
Section: A Introductionmentioning
confidence: 99%